The Effect of Cooking Methods of Several Varieties of Rice on Zinc Bioavailability Determined Using Experimental Rats - Deni Elnovriza; . Rimbawan; Emma S Wirakusumah; Dadang Sukandar (Media Gizi dan Keluarga, 2001)
The specific objectives of the research were 1) to analyze zinc content of rice, 2) to analyze effect of cooking on zinc content of rice and 3) to identify the effect of cooking methods of rice on bioavailability of zinc. Zinc bioavailability was indicated by serum alkaline phosphatase activity, zinc serum and growth of Wistar rats. Boiled, steamed and puffed of Membramos, Cisadanes and Brown rice were used in this research. The results of this study showed that cooking methods affect zinc in rice. Zinc content decreased after cooking in all of cooking methods. The lost of zinc was found highest in puffed rice and lowest in steamed rice. When rats fed those rice-based diets, zinc serum was for all of treatments not significantly different. Measurement of serum alkaline phosphatase activity of rats fed steamed and boiled rice was significantly higher than control, but not for rats fed puffed rice. All rats fed treatment diets have higher growth than those fed control. Zinc bioavailability was found lower in puffed rice than steamed and boiled. Steamed rice has zinc bioavailability better than that of boiled and puffed.